Effect of C-type natriuretic peptide on craniofacial skeletogenesis in mice during the pubertal growth spurt. (July 2022) - Kashiwagi, Marina; Nakao, Kazumasa; Yamanaka, Shigeki; Yamauchi, Ichiro; Yamashita, Takafumi; Fujii, Toshihito; Ueda, Yohei; Kawai, Mariko Yamamoto; Watanabe, Takuma; Fukuhara, Shizuko; Bessho, Kazuhisa
Abstract: Objective: This study aimed to determine the effect of C-type natriuretic peptide (CNP) overexpression on craniofacial growth during the pubertal growth period in mice. Design: Six-week-old C57BL/6 mice were injected with pLIVE-Empty vectors (Control mice) and pLIVE- NPPC vectors (CNP mice) using the hydrodynamic method. Morphological analyses were performed at the age of 12 weeks. Results: Micro–computed tomography (µCT) images showed significant ( p  < 0.05) hyperplasia in the maxilla along the sagittal plane (CNP mice: 13.754 mm, Control mice: 13.215 mm). Further, the images revealed significant bone overgrowth in the sagittal direction in the sphenoid (CNP mice: 6.936 mm, Control mice: 6.411 mm) and occipital (CNP mice: 4.051 mm, Control mice: 3.784 mm) bones in the CNP mice compared with that in the Control mice. Compared with SAP-Nppc-Tg mice in previous studies, although there was no effect on nose length and nasal bone length, the effect was sufficient to improve craniofacial hypogrowth. Furthermore, CNP promoted sagittal cranial growth by increasing the thickness of the spheno-occipital synchondrosis in organ cultures and nasal septal cartilage in micromass cultures, which were derived from 6-week-old mice. Conclusions: We have previously shown that the elevated blood levels of CNP from the neonatal period affect midfacial skeletogenesis by promoting endochondral ossification using mice ( SAP-Nppc-Tg mice ). The overexpression of CNP, even in 6-weeks-old mice, promoted growth in the sagittal direction within the maxillary region. These findings indicate the therapeutic potential of CNP for the treatment of midfacial hypoplasia during the pubertal growth spurt. Highlights: C-type natriuretic peptide (CNP) stimulates endochondral ossification. CNP treatment from after birth shows midfacial hyperplasia in mice. Overexpression of CNP, even from 6-weeks-old, shows midfacial hyperplasia. CNP may affect the craniofacial growth during the pubertal growth spurt.